Comparison of the prevalence of blood group A in gastric cancer patients and blood donors (Revista Argentina de Cirugía, 2026)
Background: Gastric cancer has high incidence and mortality in Uruguay. Blood group A has been considered a risk factor for gastric cancer and has high prevalence in this disease.Objective: The aim of this study is to compare the percentage of blood group A in patients with gastric cancer and in blood donors in Uruguay.Material and methods: We conducted an observational and retrospective study. We used the sample size calculation for comparing proportions with a confidence of 95% and 80% power. The number calculated was 149 for each group. We included all the patients from Hospital Maciel and Cooperativa Médica de Florida who met the admission criteria and a population of blood donors from both institutions. The chi-square test was used and a p value < 0.05 was considered statistically significant.Results: A total of 153 patients and blood donors were included in each group. Blood group A was less common in gastric cancer patients than in blood donors (35.9% vs. 36.6%). The difference was not statistically significant between the groups studied.Conclusions: We did not find any significant difference in the percentage of blood group A in the groups compared.
Keywords: Stomach neoplasms; blood donors; A blood group